Corporate Social Responsibility in International Business - Ahmed Jawhar Mohammad; Roza Omer Hamadamin; Abdullah Saeed Omer (QALAAI ZANIST JOURNAL, 2024)
Corporate Social Responsibility (CSR) has gained significant attention in recent decades as the role of business organizations within society has evolved. CSR refers to the expectation that corporations conduct business in a responsible manner, encompassing economic, social, and environmental aspects. This paper aims to contribute to the understanding of CSR in international business by analyzing its importance and effects. The study addresses the lack of research on the significance of CSR in the international business context. It examines academic research to explore the impacts of CSR on international business and its role in achieving sustainable growth. The paper discusses the concept of CSR, its various dimensions, and its integration into business operations. Furthermore, it explores how CSR is perceived in the context of international business, highlighting the challenges and advantages faced by multinational enterprises (MNEs) when operating in foreign markets. The analysis emphasizes the strategic role of CSR in enhancing a firm’s reputation, differentiation, and legitimacy, as well as its potential to contribute to sustainable development. The study draws on the perspectives of institutional theory, legitimacy, and strategic management to shed light on the advantages of strategic CSR for MNEs. Additionally, the paper discusses the frameworks and standards available for measuring and reporting CSR performance. The findings underscore the need for companies to align their CSR initiatives with their core business strategies to effectively leverage their resources and capabilities. Ultimately, this study contributes to a deeper understanding of CSR’s implications in international business and provides insights for future research and practical applications.